2013
DOI: 10.1089/bfm.2013.0017
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β2, a Protective Intestinal Cytokine, Is Abundant in Maternal Human Milk and Human-Derived Fortifiers but Not in Donor Human Milk

Abstract: Pasteurization decreases concentrations of most cytokines and lactoferrin in DHM. TGF-β2, a protective intestinal cytokine, has comparable concentrations in HDMF to MHM despite pasteurization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…All milk donors of the Human Milk Banking Association of North America (HMBANA) are screened for potential pathogenicity or toxicity. In addition to the initial screening, HDM is pasteurized to eradicate potential viral or bacterial pathogens (Reeves, Johnson, Vasquez, Maheshwari, & Blanco, 2013). The pasteurization process alters composition of the human donor milk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All milk donors of the Human Milk Banking Association of North America (HMBANA) are screened for potential pathogenicity or toxicity. In addition to the initial screening, HDM is pasteurized to eradicate potential viral or bacterial pathogens (Reeves, Johnson, Vasquez, Maheshwari, & Blanco, 2013). The pasteurization process alters composition of the human donor milk.…”
Section: Discussionmentioning
confidence: 99%
“…The pasteurization process alters composition of the human donor milk. Although HDM is a preferable alternative to cow’s milk based infant formulas, many immunological, nutritional, and microbial factors are lost during pasteurization (Landers & Hartmann, 2013; Li et al, 2009; Reeves et al, 2013). Multiple research groups have reported that pasteurization reduces the innate immunological properties of breast milk.…”
Section: Discussionmentioning
confidence: 99%
“…While DM has many of the nutritional characteristics of MM, it is normally collected from mothers late in their lactation after a term birth, and pasteurization is needed to eliminate bacterial and viral contaminants (e.g., human immunodeficiency virus and cytomegalovirus). Hence, the nutrient composition of DM differs from that of maternal colostrum and milk after a preterm birth and pasteurization reduces the levels of important bioactive and immunological components (1,23,37). This justifies a search for alternative enteral milk diets to support body growth and GIT maturation in the preterm infant during the first weeks.…”
mentioning
confidence: 99%
“…105 Human milk contains TGF-b at concentrations as high as 1.5 mg/mL, 106 with expression influenced by maternal factors that include diet, psychosocial stress, history of allergic disease, and stage of lactation. 107 Several clinical studies have demonstrated an association between higher concentrations of TGF-b in milk and decreased risk of neonatal disease, including respiratory difficulty and allergy, 108 and a positive correlation between milk TGF-b concentrations and infant immunoglobulin production. 109 The presence of TGF-b attenuates the inflammatory response to cytokines IL-1b and to the dsRNA viral mimic polyinosinic:polycytidylic acid in primary human fetal intestinal epithelium, 110 and TGF-b in milk promotes the induction of antigenic tolerance during colonization of the neonatal intestine.…”
Section: Immunomodulatory Properties Of Transforming Growth Factor Bmentioning
confidence: 99%